Samarium strontium cobalt oxide – samarium doped ceria carbonate (SSC-SDCC) as a new potential composite cathode material for low temperature solid oxide fuel cell - Mohammad, Siti Fairus (2021)
Systematic research regarding SSC-SDC carbonate (SSC-SDCC) as composite cathode is limited despite great chemical compatibility and cell performance achieved with other low temperature solid oxide fuel cell (LTSOFC) components. LTSOFC based on SDCC electrolyte display lower of area specific resistance (ASR) with high value of stability and porosity. This study focuses to investigate the correlation of powder composition and calcination temperature on the chemical compatibility, microstructures, physical, mechanical, thermal and electrochemical performance of SSC-SDCC composite cathode. SSC-SDCC composite powders with the weight ratios of SSC toward SDCC of 50:50 (SSCB55), 60:40 (SSCB64), and 70:30 (SSCB73) were achieved using high energy ball milling (HEBM). All powders were calcined at 600,650, 700 and 750 °C, pelletized and sintered at 600 °C. Characterization include the chemical and structural, thermogravimetric, thermal expansion coefficient (TEC), morphologies and porosity were carried out. Electrochemical impedance spectroscopy (EIS) was conducted in air. The chemical compatibility and morphologies of powder and pellet, thermal expansion and porosity were mostly affected by the calcination temperature as compared to powder composition. SSCB55 was selected for EIS evaluation due for the optimum chemical compatibility with lesser appearance of secondary phase. From EIS results, the area specific resistance (ASR) value at operating temperatures 600 ℃ were ten times smaller than the ASR value offered at operating temperatures 450 ℃. The smallest ASR value was 5.06 Ωcm2 with the activation energy (Ea) of 3.99 eV from composite cathode calcined at temperatures 750 ℃. In conclusion, this study significantly contributes to the investigation of SSC-SDCC composite as potential cathode material for economical, high stability and promising energy converter devices in low temperature solid oxide fuel cell (LTSOFC).